Autorzy:Jacek Lech, Marek Pisarski, Marcin Braun
Wydawnictwo:GWO
Rok wydania:2016
Rozwiąż równania.4.63 gwiazdek na podstawie 8 opinii

Korzystamy ze wzorów:

`a^m*a^n=a^(m+n)`  

`b^m/b^n=b^m:b^n=b^(m-n)\ \ \ "dla"\ \ \ b!=0`  

 

`"a)"\ 15^(2x)*15^3=15^13` 

`\ \ \ 15^(2x+3)=15^13` 

`\ \ \ 2x+3=13`  

`\ \ \ 2x=10` 

`\ \ \ x=5`   

`ul(ul(\ \ \ \ \ \ \ \ \ \ ))` 

`"b)"\ 7^24:7^(2x)=7^4`   

`\ \ \ 7^(24-2x)=7^4`  

`\ \ \ 24-2x=4`   

`\ \ \ -2x=-20` 

`\ \ \ x=10`   

`ul(ul(\ \ \ \ \ \ \ \ \ \ ))` 

`"c)"\ 9^4*9^(3x-4)=9^15`  

`\ \ \ 9^(4+3x-4)=9^15`  

`\ \ \ 9^(3x)=9^15`     

`\ \ \ 3x=15`  

`\ \ \ x=5`   

`ul(ul(\ \ \ \ \ \ \ \ \ \ ))` 

`"d)"\ 13^(2x+7):13^7=13^6`    

`\ \ \ 13^(2x+7-7)=13^6` 

`\ \ \ 13^(2x)=13^6`   

`\ \ \ 2x=6` 

`\ \ \ x=3`   

`ul(ul(\ \ \ \ \ \ \ \ \ \ ))` 

`"e)"\ 41^(3x)/41^x=41^8`  

`\ \ \ 41^(3x-x)=41^8`  

`\ \ \ 41^(2x)=41^8`   

`\ \ \ 2x=8` 

`\ \ \ x=4`   

`ul(ul(\ \ \ \ \ \ \ \ \ \ ))` 

`"f)"\ 6^x*6^12=6^(2x)`  

`\ \ \ 6^(x+12)=6^(2x)`  

`\ \ \ x+12=2x`   

`\ \ \ -x=-12` 

`\ \ \ x=12`